Case Report: Repeated Series of Ketamine Infusions in Patients With Treatment-Resistant Depression: Presentation of Five Cases - Gałuszko-Wȩgielnik, Maria; Włodarczyk, Adam; Cubała, Wiesław Jerzy; Wilkowska, Alina; Górska, Natalia; Słupski, Jakub (Frontiers in Psychiatry, 2021)
Purpose: Approximately 30% of patients with MDD are treatment-resistant. There is an unquestionable need for new treatment strategies. Subanaesthetic doses of intravenous ketamine have a rapid antidepressant effect in treatment-resistant depression. This paper describes the efficacy of repeated series intravenous ketamine infusions as an add-on treatment in 5 TRD inpatients. Methods: Eligible patients aged 43 to 63 were given 8 ketamine infusions as an add-on treatment for patients with MDD. The subjects have readministered the intervention due to worsening depressive symptoms. Results: Of the 5 inpatients given ketamine as a series of 8 infusions, 1 underwent 3, and 4 had 2 treatment series. Four patients achieved remission after 1st series and 3 after the 2nd series of ketamine infusions. The adverse reactions were mild and transient with no sequelae. Limitations: Presented case series applies to short-term intervention with IV ketamine as an add-on therapy. The results cannot be generalized to the long-term maintenance treatment nor other ketamine formulations as well as different administration schedules and dosing. Conclusions: This case series showed efficacy and safety of the repeated series of IV ketamine treatment in TRD in MDD and BD I. The subsequent interventions were safe and observed AEs were mild and transient. Interestingly, the IV ketamine treatment at successive administrations seems to alter the major depression severity of the next affective episode. There is a critical need for further research regarding IV ketamine treatment effectiveness and long-term safety in future studies.